Conservation risks for paper collections induced by the microclimate in the repository of the Alessandrina Library in Rome (Italy) - Verticchio, Elena; Frasca, Francesca; Cavalieri, Patrizia; Teodonio, Lorenzo; Fugaro, Daniela; Siani, Anna Maria (Heritage science, 2022)
The Alessandrina Library was founded in 1667 by pope Alexander VII Chigi and is nowadays housed in the Campus of Sapienza University of Rome (Italy). Within its Ancient (mostly made of rag paper) and Modern (mostly made of contemporary paper) collections, it includes more than one million books produced from the XVI to the XXI century. In 2019, six thermo-hygrometers were deployed in its multi-storey repository to monitor temperature (T) and relative humidity (RH). Hourly T and RH data collected over 2 years allowed us to evaluate spatial and temporal thermo-hygrometric distributions and to carry out a comprehensive assessment of the climate-induced risks (mechanical, chemical, and biological deterioration mechanisms). Vertical temperature gradients associated with unstable conditions occurred in winter, resulting in upraising air flows up to the ceiling. The risky short-term RH fluctuations (EN 15757:2010) were determined to avoid mechanical stress in case of loans, relocation, and consultation. The Time Weighted Expected Lifetime (TWEL) index was used to evaluate the chemical risk for different paper-based collections as a function of their acidity and degree of polymerisation, also considering the typical response time of paper books to T and RH changes. The TWEL calculation estimated that the durability of acidic paper was around 300 years and highlighted that rag paper could be subject to cellulose hydrolysis only in summer and autumn, while contemporary paper was mostly at no risk. The risk of mould germination (Sedlbauer diagram) was possible on few days in Autumn, while the production of insect eggs (Brimblecombe empirical function) was favoured during approximately 42% of time over the year. In addition, illuminance and colorimetric measurements (performed on selected book covers) showed that light-sensitive objects could be exposed to the photodeterioration risk in the east-facing side of the repository. Although the investigation focussed on a specific case study, a similar approach could be effectively adapted to most library and archival repositories conserving paper-based collections.